2012
DOI: 10.1038/ncomms2062
|View full text |Cite
|
Sign up to set email alerts
|

Greatwall kinase and cyclin B-Cdk1 are both critical constituents of M-phase-promoting factor

Abstract: Maturation/M-phase-promoting factor is the universal inducer of M-phase in eukaryotic cells. It is currently accepted that M-phase-promoting factor is identical to the kinase cyclin B–Cdk1. Here we show that cyclin B–Cdk1 and M-phase-promoting factor are not in fact synonymous. Instead, M-phase-promoting factor contains at least two essential components: cyclin B–Cdk1 and another kinase, Greatwall kinase. In the absence of Greatwall kinase, the M-phase-promoting factor is undetectable in oocyte cytoplasm even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(130 citation statements)
references
References 52 publications
8
121
1
Order By: Relevance
“…Consequently, Cdc25 activity predominates over that of Myt1, resulting in cyclin-B-Cdk1 activation through dephosphorylation of Cdk1 (Okumura et al, 1996(Okumura et al, , 2002. Cyclin-B-Cdk1-dependent positive feedback further activates Cdc25 and inactivates Myt1 through phosphorylation of residues other than Akt sites (Hara et al, 2012;Kishimoto, 2015;Okumura et al, 2014). Finally, fully activated cyclin-B-Cdk1 causes an irreversible meiotic G2/M-phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Cdc25 activity predominates over that of Myt1, resulting in cyclin-B-Cdk1 activation through dephosphorylation of Cdk1 (Okumura et al, 1996(Okumura et al, , 2002. Cyclin-B-Cdk1-dependent positive feedback further activates Cdc25 and inactivates Myt1 through phosphorylation of residues other than Akt sites (Hara et al, 2012;Kishimoto, 2015;Okumura et al, 2014). Finally, fully activated cyclin-B-Cdk1 causes an irreversible meiotic G2/M-phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that both human and Drosophila Gwl localized in the nucleus during interphase, [17][18][19] whereas in Xenopus oocytes Gwl appeared predominantly cytoplasmic. 8 To investigate the subcellular localization of Gwl in Xenopus cells, we tagged the WT or G41S Gwl with DsRed, and expressed the recombinant proteins in Xenopus S3 cells harboring stable expression of GFP-a-tubulin. Consistent with previous (Fig.…”
Section: Dynamic Nucleocytoplasmic Localization Of Gwl During the Celmentioning
confidence: 99%
“…6,7 On the other hand, the presence of Gwl greatly reduced the amount of MPF required for mitotic entry. 8 The mechanism of PP2A/B55d inhibition by Gwl has been nicely solved with the recent identification of Endosulfine and its related family member, cAMP-regulated phosphoprotein 19 kDa, as substrates of Gwl. These substrates specifically bind to and inhibit PP2A/B55d when they are phosphorylated by Gwl.…”
Section: Introductionmentioning
confidence: 99%
“…Her beautiful live images captured Rab11a-positive vesicles, which recruit actin nucleation factors and mediate their transport to the plasma membrane (Schuh, 2011). Using dominant-negative forms of Rab11a and myosin Vb, Melina Schuh showed that they are both necessary for vesicle transport and for the meiotic spindle to migrate to the egg cortex (Holubcová et al, 2013). On the basis of these and previous data, she suggested a model in which myosindependent pulling from the spindle poles couples the spindle to the outwardsdirected movement of the vesicles and their associated actin filaments.…”
Section: Asymmetric Spindle Positioningmentioning
confidence: 99%
“…It had been known for a long time that MPF and cyclin-BCdk1 were not equal, but it was unknown what (in addition to Cdk1) constituted the missing part of MPF. However, using starfish oocytes, the keynote speaker Takeo Kishimoto (Tokyo Institute of Technology, Yokohama, Japan) demonstrated that cyclin-B-Cdk1 activity is not synonymous with MPF; instead, the MPF also requires Greatwall kinase, which phosphorylates the 19 kDa cAMP-regulated phosphoprotein (ARPP19) to suppress the activity of the phosphatase PP2A-B55 subunit, thus maintaining cyclin-B-Cdk1 substrates in their phosphorylated state (Hara et al, 2012). In Xenopus oocytes, activation of MPF and Cdk1 follows a two-step mechanism; a catalytic amount of Cdk1 is generated in a protein kinase A (PKA)-dependent manner, which then initiates a MPF auto-amplification loop to promote the full activation of Cdk1 and the resumption of meiosis.…”
Section: Cell Cycle Regulationmentioning
confidence: 99%